Sensory pollutants alter bird phenology and fitness across a continent - Senzaki, Masayuki; Barber, Jesse R.; Phillips, Jennifer N.; Carter, Neil H.; Cooper, Caren B.; Ditmer, Mark A.; Fristrup, Kurt M.; McClure, Christopher J. W.; Mennitt, Daniel J.; Tyrrell, Luke P.; Vukomanovic, Jelena; Wilson, Ashley A.; et al. (Nature (London), 2020)
Expansion of anthropogenic noise and night lighting across our planet 1 , 2 is of increasing conservation concern 3 – 6 . Despite growing knowledge of physiological and behavioural responses to these stimuli from single-species and local-scale studies, whether these pollutants affect fitness is less clear, as is how and why species vary in their sensitivity to these anthropic stressors. Here we leverage a large citizen science dataset paired with high-resolution noise and light data from across the contiguous United States to assess how these stimuli affect reproductive success in 142 bird species. We find responses to both sensory pollutants linked to the functional traits and habitat affiliations of species. For example, overall nest success was negatively correlated with noise among birds in closed environments. Species-specific changes in reproductive timing and hatching success in response to noise exposure were explained by vocalization frequency, nesting location and diet. Additionally, increased light-gathering ability of species’ eyes was associated with stronger advancements in reproductive timing in response to light exposure, potentially creating phenological mismatches 7 . Unexpectedly, better light-gathering ability was linked to reduced clutch failure and increased overall nest success in response to light exposure, raising important questions about how responses to sensory pollutants counteract or exacerbate responses to other aspects of global change, such as climate warming. These findings demonstrate that anthropogenic noise and light can substantially affect breeding bird phenology and fitness, and underscore the need to consider sensory pollutants alongside traditional dimensions of the environment that typically inform biodiversity conservation. Human-generated noise and night lighting affect breeding habits and fitness in birds, implying that sensory pollutants must be considered alongside other environmental factors in assessing biodiversity conservation.